2022
DOI: 10.1002/cpe.7289
|View full text |Cite
|
Sign up to set email alerts
|

Automated gender‐Parkinson's disease detection at the same time via a hybrid deep model using human voice

Abstract: Summary Gender and Parkinson disease (PD) identifications are critical parts to be noted from a given in human voice. Numerous artificial intelligence based methods have been proposed to detect gender and PD easily in literature. It is purposed to build an effective and a dependable simultaneously gender and PD recognition system based on feature extraction and feature selection methods in this study. First, CNN structure is used for obtaining deeper features from TQWT applied data and acoustic deep parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…For instance, 42,45 achieved 88% accuracy using the SVM and PCA-SVM methods, respectively. More recent studies, such as Ouhmida et al ( 2021) with a hybrid SVM-CNN model, achieved 98.26% accuracy, and 38 with a hybrid structure (CNN, k-NN) reported 98.9% accuracy. Although our single CNN topology does not surpass the highest reported accuracy of 99.57% by 40 using Fractional Attribute Topology (FrAT), it offers a simpler and more streamlined approach with substantial accuracy, reinforcing the viability of using a single CNN architecture for effective PD detection.…”
Section: Numerical Results and Discussionmentioning
confidence: 96%
“…For instance, 42,45 achieved 88% accuracy using the SVM and PCA-SVM methods, respectively. More recent studies, such as Ouhmida et al ( 2021) with a hybrid SVM-CNN model, achieved 98.26% accuracy, and 38 with a hybrid structure (CNN, k-NN) reported 98.9% accuracy. Although our single CNN topology does not surpass the highest reported accuracy of 99.57% by 40 using Fractional Attribute Topology (FrAT), it offers a simpler and more streamlined approach with substantial accuracy, reinforcing the viability of using a single CNN architecture for effective PD detection.…”
Section: Numerical Results and Discussionmentioning
confidence: 96%
“…Two groups of studies [ 48 , 73 ] from UCI data sets were found to be suitable for meta-analysis due to the homogeneity between studies. The first group consisted of 15 studies using a data set containing voice recordings from 188 participants with PD and 64 HC participants [ 40 , 42 , 44 , 48 , 55 , 61 , 64 , 68 , 99 , 119 , 121 , 122 , 124 , 126 , 127 ]. The second group consisted of 5 studies [ 53 , 57 , 60 , 71 , 100 ] using voice recordings from 20 participants with PD and 20 HC participants ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 70 studies collected data for a specific study and 75 studies gathered data from an available data set. Sakar et al (2013) [73] and Sakar et al (2019) [48] are 2 different data sets donated to the UCI (University of California, Irvine), which have been used in 15 different included studies in this SLR; 5 studies [53,57,60,71,100] used the UCI data set containing 20 participants with PD and 20 HC participants, and 15 studies [40,42,44,48,55,61,64,68,99,119,121,122,124,126,127] used the UCI data set having 188 participants with PD and 64 HC participants from the same source. UCI and Coswara provide data sets that can be accessed and downloaded without any additional application [73,189].…”
Section: Data Characteristicsmentioning
confidence: 99%